The Tracker Organ Revival in America - Pape, Uwe 1936- (Boston Houghton Mifflin Harcourt, 2021)
195 Dispositionen, Werkverzeichnisse von 99 Orgelbauern, Lebensläufe von 81 Orgelbauern. Mit einem Vorwort von H. J. Busch und Beiträgen von E. P. Biggs, G. Bozeman, J. Fesperman, C.B. Fisk, J. von Glatter-Götz, J. Lauder, R. Redman, H. Wolff u.a.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Organ; Organ registration; Organology; USA